MOLECULAR MARKER ANALYSIS OF SELECTED RICE LINES FOR AEROBIC TRAITS UNDER WATER LIMITED CONDITIONS TER LIMITED CONDITIONS - KANIKA RANI, KULDEEP KUMAR; RAJINDER KUMAR JAIN AND SUNITA JAIN, RAHUL KUMAR MEENA, MAHAVIR (The Bioscan, 2018)
In present scenario it is necessary to be a step ahead conferring with water scarcity. Aerobic rice is a newly developed water efficient rice system which flourishes under unsaturated and non-flooded condition. High yield in aerobic method of cultivation were ascribed to genotypes tolerance to moisture. In this context to assess the influence of water use efficiency on grain yields in rice genotypes, field experiments were conducted. Segregating aerobic x lowland progenies [MAS25/HKR47 (F3 & F4); MASARB25/HKR47 (F3 & F4 ) and [MASARB25/HKR47)/ HKR47 (BC1F3)] were evaluated for various physio-morphological and/or root traits and SSR markers linked to the traits promoting aerobic adaptation. In all the populations, enormous variation was observed for various physiomorphological and root traits. In these populations, significant positive correlation was observed between yield per plant with plant height, effective number of tillers per plant, grain length/breadth ratio, 100 grain weight, root length and/or root biomass. A total of 40 SSR markers linked to the QTL promoting aerobic adaptation (as found by others) were used for the parental screening. Presence of these traits was ascertained using single marker analysis. A total of 3-7 polymorphic microsatellite markers linked to the traits promoting aerobic adaptation were used to analyze the segregation in the selected F4 and BC1F3 plants derived from the five crosses. In SSR marker analysis most of the selected plants were found to posses desirable alleles for the markers reported earlier to be linked with the aerobic adaptation traits.